Occurrence of Intestinal Parasites in Alouatta caraya of the Zoobotanical Park of Teresina, Piauí, Brazil - Ferreira da Silva, Maylane Tavares; Aquim, Eric Carvalho; de Sousa, Tiago Paixão Ribeiro; Gomes, Naelson Railson de Sousa; de Vasconcelos, Auan Rangel Oliveira; Andrade Silveira, Camila Cristina de Oliveira; Junior Costa, Franciso Michael; Evangelista, Luanna Soares de Melo (Acta Scientiae Veterinariae, 2018)
Background: The animals of the genus Alouatta are popularly known as Bugios, barbados, roncadores and guaribas, being the neotropical primates better studied in the world. They originate in South America, with records in Argentina, Bolivia, Paraguay and Uruguay. Because of their migrations, many are found debilitated and taken to captivity until their rehabilitation and most cannot be reinserted in nature. They tend to live in extensive areas, having a low resistance against parasitic infections because of low exposure and when kept in captivity, the risks of these infections increase. Some diagnostic techniques can aid in the detection of parasites of zoo animals and can identify the parasitic fauna of these animals. The objective of this work was to investigate and report the presence of intestinal parasites in a female Bugio-preta (Alouatta caraya) captive of the Zoobotanical Park of the municipality of Teresina, Piauí, Brazil. Case: The animal presented a constipation signs before clinical signs of apathy, anorexia, diarrhea and weight loss, suggestive signs of parasitosis, Sterile papers were placed on the floor of the animal enclosure and collected fresh stools shortly after defecation, the feces were removed using gloves, stored in a capped containers, identified and taken to the Laboratory of Parasitology of the Department of Parasitology and Microbiology of the Federal University of Piauí, for further evaluation. The fecal samples were submitted to the techniques of spontaneous sedimentation (HPJ), centrifugation-flotation (Faust) and flotation method in hyper saturated sucrose solution (Willis-Mollay), obtaining slides that were analyzed under an optical microscope in the 10x and 40x objective, confirming the presence of ascarids and hookworms. Discussion: The results showed the presence of eggs of Ascaris sp. and Ancylostoma sp. in all of the analyzed techniques, thus maintaining an alert, since they are considered helminths of zoonotic character. The general state of the animal may have influenced considerably the result of mixed infection by helminths, since it had episodes of diarrhea and was skinny at the time of diagnosis. Diarrheal feces and slimming favor the encounter of mixed infection, since the parasites in large quantity can cause to their hosts a decrease in the absorption of nutrients and an intestinal peristalsis increase. Other works with primates also revealed the presence of parasites in animals, including protozoans. The collection moment and evaluation of the fecal samples of the Bugio coincided with the rainy period in the region. This fact can favor the increase of eggs and larvae of parasites in the environment and, consequently, can contaminate the animals. Regarding to sanitary management of zoos, areas full of plants and trees make it difficult to hygienize the enclosures and in these places is common the presence of other animals that can serve as carriers of pathogens. The available diagnostic great relevance to assess the degree of animal infection, the possibility of transmission and the sanitary conditions of the environment. It was concluded that the female Bugio of the Teresina Zoobotanical Park was parasitized by ascarids and hookworms and the techniques of parasitological exams performed represented great relevance for the early diagnosis and an appropriate treatment, being able to be used for the control of diseases parasites, mainly zoonoses.